High-Resolution Single-Beam Bathymetry and IHO S-44 Uncertainty Benchmarking for Damaged-Pile Validation at Bullnose Jetty, Lagos, Nigeria - Alfred Sunday Alademomi; Joseph Olayemi Odumosu; Stephen Olushola Oladosu (Sriwijaya Journal of Environment, 2026)
Background: Coastal port infrastructure operates in dynamic tidal environments where seabed change threatens structural safety, yet high-resolution, standard-benchmarked bathymetric validation of damaged and replacement piles is scarce for West-African ports. Objective: To characterise seabed conditions and validate proposed replacement piles at Bullnose Jetty, Apapa Port Complex, Lagos Lagoon, Nigeria, ahead of piling and repair. Methods: A single-beam echo-sounder with RTK-GNSS and 10-minute tidal reduction produced a 0.1-m grid, interpolated by kriging (Surfer 16). The survey polygon was stratified into four hydrographic sub-zones (n = 108 nodes); six parameters were analysed by one-way ANOVA with Tukey HSD, Pearson correlation, multiple regression and PCA, and benchmarked against IHO S-44 (Ed. 6.0.0). Results: Corrected depths ranged 10.1–13.2 m and differed significantly among zones (11.66±0.86 m; F(3,104)=131.0, p<0.001, η²=0.79), deepening from the quay apron (10.65±0.35 m) to the central channel (12.76±0.42 m). Achieved total vertical uncertainty (0.23–0.27 m, k=2) met IHO Order 1a everywhere and Special Order in sheltered zones, and was governed by roughness and depth (R²=0.82). PCA captured 86.3% of variance in two components. No obstructions occurred at piles A-38/39/40; the broken pile P39A was mapped on the seabed. Conclusion: The reproducible, IHO-benchmarked protocol confirms safe pile placement and supports routine hydrographic monitoring of Lagos-area port infrastructure.